Generation Victoria (GenV): protocol for a longitudinal birth cohort of Victorian children and their parents - Elizabeth K. Hughes; William Siero; Alisha Gülenç; Susan A. Clifford; Tony Frugier; Simon M. Hall; Jatender Mohal; Kathryn North; Natasha Zaritski; Sharon Goldfeld; Richard Saffery; Melissa Wake (BMC Public Health)
Abstract Background In a world confronted with new and connected challenges, novel strategies are needed to help children and adults achieve their full potential, to predict, prevent and treat disease, and to achieve equity in services and outcomes. Australia’s Generation Victoria (GenV) cohorts are designed for multi-pronged discovery (what could improve outcomes?) and intervention research (what actually works, how much and for whom?). Here, we describe the key features of its protocol. Methods GenV is a whole-population longitudinal platform open to all ≈150,000 children born within a two-year window and residing in the state of Victoria and their parents. GenV is guided by its 6 principles of Inclusivity, Collaboration, Sustainability, Enhancement, Systematised Processes and Value and enabled by large-scale biobanking, IT and novel high-throughput technology infrastructure. Successive recruitment phases were designed to maximise GenV’s inclusivity: (1) a smaller Advance Cohort from December 2020; (2) Newborn recruitment, with presence in 58 Victorian maternity services supporting face-to-face approach to parents of babies born 4 October 2021–3 October 2023; (3) Intensive remote recruitment to mid-2024 targeting those missed around birth; and (4) Ongoing indefinite enrolment of in-age children and their parents. Participants consent to universal (1) data linkage (e.g., state and federal physical and mental health, education, social, geospatial, ecological); (2) biosamples storage and use (e.g., residual clinical pregnancy and newborn screening, GenV-collected perinatal parent/infant saliva); (3) phenotypic and biosamples collection waves at child ages 6, 11 and 16 years, likely in schools and remotely for parents; and (4) opportunities for collaborative research integrated into GenV as a population registry (e.g., trials, natural experiments, depth subcohorts). Many participants supplement universal data with additional biosamples (e.g., infant stool, breast milk) and brief digital remote ‘GenV and Me’ assessments over the first 5 years. GenV will make all research data available, adhering to the principles of Open Science. Discussion Launched in the COVID-19 pandemic and committed to diversity and inclusivity, GenV’s parallel consented child and pre-midlife cohorts will be positioned to help address today’s pressing issues such as chronic mental and physical health conditions, inequity, public health crises such as pandemics, and climate harm. Trial registration ClinicalTrials.gov: NCT05394363; retrospectively registered 23 May 2022 (8 months into recruitment).